Proteomic analysis unveils host-parasite interactions in Aedes togoi infected with Dirofilaria immitis and Brugia pahangi - Wei Yin Vinnie-Siow; Van Lun Low; Hwa Chia Chai; Yvonne Ai-Lian Lim; Tiong Kai Tan (PLoS ONE, 2025)
Background Mosquitoes serve as the primary vectors responsible for transmitting canine filariasis, yet understanding the molecular interactions between filarial parasites and their vectors is a significant challenge.. Therefore, employing a proteomic approach is crucial for elucidating the protein expressions profile in mosquitoes, allowing the tracking of biochemical changes during parasite development and survival within the mosquito. To infer the protein response of mosquitoes to filarial infections, Aedes togoi was inoculated with canine filarial parasites, Dirofilaria immitis and Brugia pahangi, and maintained for 14 days prior before dissection to collect their cuticular tissue proteins for Liquid Chromatography-Tandem Mass Spectrometry (LC-MS/MS) analysis. Actin and prophenoloxidase, recognized as defence proteins, exhibited upregulation in groups inoculated with D. immitis and B. pahangi. Most proteins in glycolysis, gluconeogenesis, and the TCA cycle were upregulated in both groups, except for dihydrolipoyl dehydrogenase, vital for pyruvate decarboxylation, which was downregulated, while glucose-1-phosphate uridylyltransferase, essential for glycogen production, was expressed despite its absence in the control. Additionally, a pathway related to tyrosine metabolism, involving aspartate aminotransferase, AAEL010442-PA, 4-hydroxyphenylpyruvate dioxygenase, aspartate aminotransferase, and homogentisate 1,2-dioxygenase, was expressed. This study has addressed gaps in understanding the protein response of mosquitoes infected with filarial parasites, shedding light on host defence mechanisms and potential metabolic adaptations, thereby enhancing our comprehension of filariasis infection mechanisms.